DECODING WAVELET TRANSRORMATIONS IMAGES IN TWO-LEVEL SPACE - Бараннік, В.; Гуржій, П.; Ширяєв, А. (Science-based technologies, 2011)
This paper developed a method for recovery of transformants of discrete wavelet transforms with controll able losses based on a dynamic two-level decoding. This method allows obtaining images with a given qua lity with a minimum amount of overhead and reducing processing time.